Cumplimiento de la meta 5 y la mejora en los servicios de agua y saneamiento del Distrito de Lagunas Provincia de Alto Amazonas período 2019 – 2023 - Suarez Burga, Francisco (2024)
Goal 5 is a government initiative through the Ministry of Economy and Finance's municipal incentives program to improve the sustainable quality of drinking water and sanitation services. Its main objective is to close the gaps in access to and consumption of safe water and sanitation in rural areas of Peru. This research relates the variables of compliance with Goal 5 and the improvement of water and sanitation services in the Lagunas district, Alto Amazonas province, from 2019 to 2023. A quantitative approach was used, with a descriptive-correlational, non-experimental, longitudinal study level. The study population included 14 municipal officials, and the sampling was census type (population = sample), using a questionnaire for data collection. The reliability of the instrument was obtained with an acceptable Cronbach's Alpha of 0.788. The results were divided into two statistical blocks: descriptive and inferential. In the descriptive analysis, it was found that for Variable 1: Goal 5, 86% determined that Goal 5 was met in the 2019-2023 period, while 14% indicated that it was partially met (According to the MEF, the goal is considered met if 80% of the evaluated activities are carried out). Regarding Variable 2: improvement in water and sanitation services, 86% reported that there was no improvement, and 14% of the sample considered it as few improvements. In the inferential analysis, the Spearman's Rho statistic shows an inverse correlation coefficient of -0.838, which indicates that the behavior of the variables is antagonistic, since when one increases, the other decreases. Therefore, there is a relationship of association or interdependence between V1 Goal 5 and V2 Improvement in Water and Sewerage Services. The significance level (bilateral) is 0.000<0.05, therefore the null hypothesis Ho is rejected and the general hypothesis Hi is accepted. Analyzing the results, we can conclude that compliance with Goal 5 does not favor at all the improvement of water and sanitation services in the Lagunas district, Alto Amazonas province. This means that the greater the incentive, the less benefit the population will have in this area.